Prevention of the technological addictions in adolescence (Journal of Parents and Teachers, 2017)
Technological addictions (social networks, mobile and video games) are one of the current main problems presented by adolescents in relation to Information and Communication Technologies (ICT). This paper describes the main characteristics of these new addictions and presents the ADITEC, an instrument whose objectives are the evaluation and prevention of these addictions. ADITEC is a tool specially designed to be applied in educational settings, with homeworks that can be supervised by parents.
Keywords: technological addictions; prevention; adolescence; educational guidance